2021
DOI: 10.1021/acs.jnatprod.0c00829
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids from the Aerial Parts of Salvia plebeia with Inhibitory Activities on Proprotein Convertase Subtilisin/Kexin Type 9 Expression

Abstract: Phytochemical investigation of the methanol extract of the aerial parts of Salvia plebeia aided by a proprotein convertase subtilisin/kexin type 9 (PCSK9) mRNA expression screening assay in HepG2 cells led to the identification of 19 compounds including one new norsesquiterpene (1), six new eudesmane sesquiterpenoids (2−5, 8, and 11), and 12 known compounds. The structures of all compounds were elucidated by interpretation of their 1D and 2D NMR spectroscopic and MS data. Furthermore, computational prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…As part of our ongoing project to discover PCSK9 expression inhibitory compounds from medicinal plants [17][18][19][20], the n-BuOH-soluble fraction of the aerial parts of E. koreanum was selected for further investigation due to its initial PCSK9 mRNA expression inhibitory activity (Supplementary Material Figure S1-1). However, there are no reports regarding PCSK9 inhibitory substances from this plant.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing project to discover PCSK9 expression inhibitory compounds from medicinal plants [17][18][19][20], the n-BuOH-soluble fraction of the aerial parts of E. koreanum was selected for further investigation due to its initial PCSK9 mRNA expression inhibitory activity (Supplementary Material Figure S1-1). However, there are no reports regarding PCSK9 inhibitory substances from this plant.…”
Section: Introductionmentioning
confidence: 99%
“…The known structure compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were identified by comparison of their spectroscopic data with the reported values, as 5-O-methylembelin (3), 20 5-O-methylrapanone (4), 21 9-hydroxy-(9S,10E,12Z,15Z)-octadecatrienoic acid (5), 22 9-oxo-(10E,12E)-octadecadienoic acid (6), 23 9-oxo-(10E,12Z)-octadecadienoic acid (7), 23 2,3-dihydroxypropyl-(10Z,13Z)-nonadecadienoate (8), 24 2,3-dihydroxypropylpentadecadienoate ( 9), 25 1-monopalmitoyl-rac-glycerol (10), 26 monononadecanoin (11), 27 methyl linoleate ( 12), 6 linoleic acid (13), 6 oleic acid ( 14), 24 capric acid (15), 28 lauric acid (16), 29 palmitic acid (17), 30 stearic acid (18), 31 (+)-demethoxylpinoresinol (19), 6 (+)-pinoresinol (20), 6 trans-cinnamic acid (21), 32 and cis-ferulic acid (22). 33 The known compounds (3)…”
Section: Resultsmentioning
confidence: 99%
“…PCR analysis was performed according to the previously reported method. The following specific primer sets were used (5′ to 3′): GAPDH: GAAGGTGAAGGTCGGAGTCA (forward), AATGAAGGGGTCATTGATGG (reverse); PCSK9GGGCATTTCACCATTCAAAC (forward), TCCAGAAAGCTAAGCCTCCA (reverse); IDOL­(MYLIP): ACGGTCACCAAGGAATCTGGGA (forward), CCTTCAAGTCACGGCTATACTGC (reverse); LXR-α­(NR1H3): TGGACACCTACATGCGTCGCAA (forward), CAAGGATGTGGCATGAGCCTGT (reverse); SREBP1: ACTTCTGGAGGCATCGCAAGCA (forward), AGGTTCCAGAGGAGGCTACAAG (reverse) and SREBP2: CTCCATTGACTCTGAGCCAGGA (forward), GAATCCGTGAGCGGTCTACCAT (reverse). Gene-specific primers were custom-synthesized by Bioneer (Daejeon, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is cooling in nature and pungent to taste, effectively clears away heat and toxins, cools the blood, and dissipates blood stasis, diuresis, and swelling [4][5][6][7]. Previous pharmacological studies have shown that S. plebeia has antiasthmatic, anti-bacterial, and anti-oxidant effects [8][9][10][11][12]. The plant mainly contains flavonoids, terpenes, phenolic acids, volatile oils, phytosterols, and other compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%